2005
DOI: 10.1007/s00606-004-0237-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the absolute configuration of the basal/flagellar apparatus and evidence of centrin during male gametogenesis in Chara contraria var. nitelloides (Charales, Charophyta)

Abstract: The absolute configurations of the basal/flagellar apparatus during male gametogenesis of Chara contraria var. nitelloides (Charales, Charophyta) were carefully analysed. Emphasis was placed on the changes in the angles and lengths of the basal bodies, the microtubular root angles and the development of the distal as well the proximal connecting fibers. Six principal stages were recognized: a) parallel, non-axonemal, developing basal bodies connected by a non-striated, proximal fiber; b) non-parallel, non-axon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Only a high-resolution electron tomographic study of this region will distinguish between these two scenarios. The exact composition of the stellate array is not known, but ultrastructural immunolocalization studies in Chlamydomonas (Geimer & Melkonian, 2005), Chara (Vouilloud et al, 2005;Jin & Hasenstein, 2009) and Ginkgo (Vaughn & Renzaglia, 2006) have shown that centrin is localized to the same area. The occurrence of centrin is widespread in sperm cells and has been associated with fibres attached to basal bodies of charophycean algae, and the amorphous zone of monilophytes (Vaughn et al, 1993).…”
Section: Elongation Of the Basal Bodymentioning
confidence: 99%
“…Only a high-resolution electron tomographic study of this region will distinguish between these two scenarios. The exact composition of the stellate array is not known, but ultrastructural immunolocalization studies in Chlamydomonas (Geimer & Melkonian, 2005), Chara (Vouilloud et al, 2005;Jin & Hasenstein, 2009) and Ginkgo (Vaughn & Renzaglia, 2006) have shown that centrin is localized to the same area. The occurrence of centrin is widespread in sperm cells and has been associated with fibres attached to basal bodies of charophycean algae, and the amorphous zone of monilophytes (Vaughn et al, 1993).…”
Section: Elongation Of the Basal Bodymentioning
confidence: 99%
“…B2 and its associated R3 and R4 form a unit that is developmentally equivalent to B1 and its associated R1 and R2, but with a 180°rotation (Figure 3a). A distinctive multilayered structure (MLS) of variable size is connected to R1 in certain 'prasinophytes', in the zoospores and sperm of streptophyte algae, and in the sperm of most non-flowering land plants (Moestrup, 1978;Stewart and Mattox, 1978;Melkonian, 1980Melkonian, , 1982O'Kelly and Floyd, 1983;Vouilloud et al, 2005) (Figures 3b-d). Red algae lack a flagellar apparatus altogether, which is highly unusual for eukaryotes, and knowledge of the glaucophyte flagellar apparatus is currently incomplete (Mignot et al, 1969;Kies, 1979Kies, , 1989.…”
Section: Plantae (Green Algae Land Plants and Relatives)mentioning
confidence: 99%
“…R1 is associated with an MLS in the flagellated stages of streptophyte lifecycles ( Coleochaete , Chara , Klebsormidium and the sperm of liverworts, mosses, ferns, Ginkgo and cycads), and in some prasinophytes (e.g. Cymbomonas , Halosphaera and Pterosperma ), which are inferred to have retained many ancestral states for the Plantae as a whole (Carothers and Kreitner, ; Moestrup, ; Melkonian, ; Li et al ., ; Graham and Wilcox, ; Vouilloud et al ., ; Archibald, ). Interestingly, an early diverging streptophyte, Mesostigma viride , has two MLSs, one associated with R1 and one associated with R3 (Rogers et al ., ).…”
Section: Homologous Elements In Different Mtocsmentioning
confidence: 99%
“…2003, Kotta et al. 2004, Vouilloud et al. 2005), while no research has been conducted on their larvicidal effect.…”
mentioning
confidence: 99%
“…According to the summaries of Zaneveld (1940), Imahori (1954), and Pal et al (1962), it was Caballero (1919), Buhot (1927), and Matheson and Hinman (1928) who claimed that at least some species of charophytes had distinct larvicidal properties, but Swellengrebel (1924), Blow (1924), and Pal et al (1962) proved that charophytes did not exert any deleterious effect on the development of mosquito larvae. In recent years, research of charophytes has focused on their physiological activities, ecological characters, and taxonomy (Lan et al 2003, Kotta et al 2004, Vouilloud et al 2005, while no research has been conducted on their larvicidal effect.…”
mentioning
confidence: 99%